AN ANALYSIS OF HUMOR EXPRESSIONS IN âTHE CHINESE WOMANâ EPISODE OF âSIENFELDâ - Wulandari, Eka (VISION, 2014)
ABSTRACT Seinfeld is one of the most popular situation comedies aired in USA televisions. It becomes quite popular since it shows everyday situations in a humorous way. People can see themselves dealing with the same situations as shown in its episodes. This research is conducted to find out about the forms of humor expression employed by the characters and to describe key factors employed in the episode which causes humor in one of the episode of Seinfeld, entitled The Chinese Woman. It also used the pragmatic approach. The data analysis shows the findings that there are three types of humor expression. They are assertive form, directive form, and expressive form. Meanwhile, the key factors causing humor in The Chinese Woman are the violations of cooperative principle and politeness principle, and the exploitation of irony principle. Â Keywords: situation comedy, humor, pragmatic